The Influence of Work Environment, Work Discipline, and Work Stress on Employee Performance - Rahakbauw, Nindi Graciosa; Aryati, Ana Sofia (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
The urgency of this research lies in the importance of understanding factors influencing employ-ee performance in a competitive industry, particularly to enhance productivity at PT Waleta Asia Jaya Salatiga. This study aims to identify the influence of work environment, work discipline, and work stress on employee performance. This explanatory quantitative research method was used to examine the relationships and interactions among these variables through hypothesis testing. Data were collected through a Likert-scale questionnaire distributed to employees of PT Waleta Asia Jaya Salatiga, with purposive sampling techniques and a total sample of 176 re-spondents. Analysis was conducted using multiple linear regression with SPSS version 29 soft-ware. The findings indicate that work environment (X1) and work discipline (X2) have a positive and significant effect on employee performance (Y), while work stress (X3) has a negative and significant impact on performance. The Adjusted R Squared value of 0.622 suggests that work environment, work discipline, and work stress contribute 62.2% to employee performance, while the remaining 37.7% is influenced by other factors outside this research model. This study offers novelty by integrating these variables together in this sector and practical implications for com-panies to enhance performance through more effective management of work environment and employee stress.